Asymmetric Synthesis of Vicinal Tetrasubstituted Diamines via Reductive Coupling of Ketimines Templated by Chiral Diborons. Issue 17 (17th March 2023) - Zhou, Mingkang; Lin, Yaodong; Chen, Xiao‐Xuan; Xu, Guangqing; Chung, Lung Wa; Tang, Wenjun
Abstract: We herein describe the chiral diboron‐templated asymmetric homocoupling of aryl alkyl ketimines, providing for the first time a series of chiral vicinal tetrasubstituted diamines with excellent ee values and good to high yields. The powerful and efficient diboron‐participated [3, 3]‐sigmatropic rearrangement is successfully demonstrated by the homocoupling of a variety of ketimines thanks to the rational design and engineering of chiral diborons. Systematic DFT studies suggest that two chiral diborons adopt different conformational assembling strategies to couple the diboron template with ketimine substrates in their tight concerted transition states to ensure the excellent enantioselectivities. The synthetic value of chiral vicinal tetrasubstituted diamines is demonstrated by the asymmetric α‐bromination of aliphatic aldehydes by employing a chiral vicinal tetrasubstituted diamine‐based organocatalyst. Abstract : A series of chiral vicinal tetrasubstituted diamines are prepared with high ee values and good to excellent yields via an unprecedented chiral diboron‐templated asymmetric homocoupling of aryl alkyl ketimines. The synthetic value of these chiral vicinal tetrasubstituted diamines is demonstrated by the development of efficient organocatalysts for the asymmetric α‐bromination of aliphatic aldehydes.